Hematology and Plasma Chemistry Reference Values in Nursehound Shark (Scyliorhinus Stellaris) Maintained Under Human Care - Morón-Elorza, Pablo; Rojo-Solis, Carlos; Steyrer, Christine; Álvaro-Álvarez, Teresa; Valls-Torres, Mónica; Encinas, Teresa; García-Párraga, Daniel (Frontiers in Veterinary Science, 2022)
Studies determining baseline hematological reference intervals (RI) in elasmobranchs are very limited. In this study, blood samples were collected from 94 clinically healthy Nursehound Shark (Scyliorhinus stellaris) maintained under human care. Median (RI) in major leukocyte types were similar to other Carcharhinid sharks as lymphocytes were the predominant leukocyte with 38.0 (28.2-53.5) %, followed by coarse eosinophilic granulocytes with 20.0 (12.2-31.7) %, fine eosinophilic granulocytes with 6.0 (1.2-12.8) %, monocytes with 2.0 (0.0-6.0) %, and neutrophils with 2.0 (0.0-6.0) %. Nursehound Shark produced granulated thrombocytes, which were classified as granulocytes and represented 28.5 (12.4-39.7) % of all leukocytes. Median (RI) manual red blood cell and white blood cell counts were 177.50 (132.50-210.00) x 109 cells/l and 8.26 (5.24-14.23) x 109 cells/l, respectively. Median (RI) plasma chemistry values showed alkaline phosphatase 7.7 (4.2-13.0) U/l, aspartate aminotransferase 7.6 (3.3-17.1) U/l, blood urea nitrogen 281.6 (261.2-305.0) mmol/l, calcium 3.97 (3.59-4.47) mmol/l, total cholesterol 2.04 (1.02-3.91) mmol/l, chloride 233.0 (215.2-259.0) mmol/l, iron 3.79 (1.74-6.93) µmol/l, glucose 0.87 (0.47-1.44 mmol/l), potassium 3.8 (2.9-4.6) mmol/l, sodium 243.0 (227.7-271.0) mmol/l, phosphorus 1.58 (1.13-2.10) mmol/l, total protein 24.0 (20.0-35.0) g/l and triglycerides 0.97 (0.49-3.35) mmol/l. Creatine kinase, gamma glutamyl transferase, and lactate dehydrogenase levels were below the instrument reading range.